Latinx* popular culture imaginaries: examining Puerto Rican children's social discourses in interpreting telenovelas. Issue 1 (2nd January 2017) - Medina, Carmen Liliana; Costa, María del Rocío; Soto, Nayda
Abstract: In this paper, we present a collaboration project within one urban Puerto Rican classroom, focused on constructing a critical literacy inquiry curriculum grounded in the students' out-of-school literacy practices in their communities, including their experiences with media and popular culture. We focused on a critical literacy and media inquiry unit centered on the students' self-selected subject of the telenovela. Here, we examine one student's work to highlight two overarching findings: (1) the visibility of the students' complex understanding of the media landscapes in telenovelas, particularly the construction of dominant social discourses across telenovela worlds, and (2) the ways that bringing children's mediatized cultural imaginaries in their creative work supports an approach to literacy in classrooms, where explorations of discourses of power emerge from the students' knowledge. In order to articulate how children actively examine and construct discourses across multiple social worlds, we examine these findings using the Four Resource Model, and elements of discourse analysis, as theoretical and analytical frameworks, focusing on the construction of identities, worlds and meanings in relation to the social discourses of telenovelas.